Nikon creative lighting system digital field guide - Edwards, Benjamin. (Wiley Pub., 2012)
This book does include the nuts and bolts information usually included in a standard manual. However, it also covers tips and advice. It also includes sample images and set up diagrams that explain how a short was created using the Nikon CLS